Penerapan Hukum Adat Dalam Penyelesaian Perkara Pidana Melalui Konsep Restorative Justice di Kabupaten Rokan Hulu Provinsi Riau - Elmayanti; Mukhlis R (Fakultas Hukum Universitas Riau, 2022)
The restorative justice approach is a paradigm that is used as a framework for a criminal case handling strategy aimed at responding to dissatisfaction with the work of the current criminal justice system. Where the conventional criminal case settlement process is very complicated and takes a long time to arrive at a judge's decision, the litigants may not even necessarily get the justice or satisfaction they expect. Restorative justice is a concept of responding to the development of the criminal justice system by focusing on the need for community involvement and victims who feel excluded from the mechanisms that work in the current criminal justice system. The purpose of this study was to determine the application of customary law in the settlement of criminal cases through the concept of restorative justice in Cipang Kanan Village, Rokan IV Koto, Rokan Hulu Regency, Riau Province. This type of research is sociological and juridical, with an emphasis on field research; it is descriptive because it intends to describe the reality under study clearly and systematically. The community in Cipang Kanan Village always prioritizes deliberation in every activity, especially in matters relating to the resolution of disputes, so that every problem that occurs in the community always involves the role of traditional leaders in its resolution. This is a reflection of the custom that they have always implemented, where every dispute always uses peace efforts by mediation and is followed by customary sanctions that must be met by perpetrators who have violated customary provisions.